Educative actions in health promotion for aging: the experience of UNATI/UERJ elderly assistance nucleus - de Assis, Mônica; Carvalho Pacheco, Liliane; Garcia de Menezes, Maria Fátima; de Jesus Bernardo, Maria Helena; Vigné Alvarez de Steenhagen, Claudia Helena; Lima Tavares, Elda; Martins dos Santos, Débora (O Mundo da Saúde, 2007)
This paper presents the experience of the Program of Educative Actions in Health Promotion for Aging, maintained by the Elderly Assistance Nucleus, an outpatient clinic of UERJ’s (Rio de Janeiro State University) Third Age Open University. It is an interdisciplinary program that includes several educational activities, open to the elderly and users in general. Its activities include waiting room groups, closed groups (Meetings with Health), open groups (Health “Wheel”) and the production of educational material, such as folders and boards. The work is based on a view of health integrated to quality of life, and sees education as a dialogue, interchange of experiences, partnership, respect to others, reflection, the questioning of reality and the search for possible alternatives and choices. Elderly needs are considered in the educational process, boosting their capacity to learn, create, decide, respecting the particularities of the aging process. The experience honors and brings to discussion the complexity and richness of the educational dimension of health, consolidating itself as a strategic field for professional training and development of a model of assistance based on comprehensive care and practicaltheoretical articulation for health promotion. On a teaching level, the work stimulates a new sensibility on the professional culture, capable of including others and their knowledge, considering the social, economic and cultural conditions and their relationships with health. On a service level, the program represents a “door opening” to participation, bringing together professionals and the population, strengthening the vow to quality assistance, centered on human bonding, on responsibility and on sharing the challenges to quality of life and health on aging.